Legal Implications of Regulatory Voids in Evidence Management and Efforts to Strengthen Sanctions for Negligent Officers in Preserving Evidence - Iwansyah Iwansyah; Megawati Barthos (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the role and challenges of evidence management in the criminal justice system in Indonesia, focusing on issues such as damage, loss, and inconsistency of evidence, which can significantly impact the evidentiary process and the outcome of criminal trials. Effective evidence management is crucial in ensuring the integrity of the legal process and upholding justice. The study employs a normative legal approach using statutory and conceptual methods to analyze the legal provisions that govern the confiscation, storage, and handling of evidence, specifically referring to Article 39 of the Indonesian Criminal Procedure Code. This article sets forth the procedures for evidence confiscation by law enforcement authorities and outlines their responsibilities in maintaining and presenting the evidence in court. A major concern in the management of evidence is the potential damage or loss of evidence during the investigation or trial stages. Such issues undermine the validity of the evidence and can lead to unjust verdicts, affecting the principle of fairness in the criminal justice process. Additionally, inconsistencies in how evidence is handled, including mislabeling or failure to maintain chain-of-custody records, can raise doubts about the authenticity of the evidence and erode public trust in the legal system. This study highlights how these problems directly impact the judicial outcomes and the overall credibility of the justice system in Indonesia. Furthermore, this study discusses the challenges faced by law enforcement agencies and legal professionals in returning evidence that does not conform to its original condition. The return of damaged or improperly handled evidence not only violates the principle of justice but also affects the accused's right to a fair trial.